Pengembangan Perangkat Pembelajaran PBL (Problem Based Learning) Berbasis STEM (Science, Technology, Engineering, and Mathematics) Untuk Meningkatkan Keterampilan Berpikir Kritis dan Keterampilan Komunikasi Siswa Kelas X SMA - Hestari, Selvira; Ibrohim, Ibrohim; Gofur, Abdul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to produce STEM-integrated PBL learning tools on Ecosystems and Environmental Change material that are valid for training students' critical thinking and communication skills. Development of learning tools using the ADDIE model. The validation results of the learning tools developed were stated to be very valid based on the average rating of the learning design expert validators and field practitioners. The results of the paired t-test showed that there were differences in the mean scores of the pre-test and post-test student’s critical thinking skills. The average score for each aspect of students' communication skills is included in the good criteria. Based on the results of the study it can be concluded that PBL learning tools can help train students' critical thinking and communication skills.